2008
DOI: 10.1103/physrevb.78.115311
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous dephasing scattering rate of two-dimensional electrons in double quantum well structures

Abstract: The results on the measurement of electrical conductivity and magnetoconductivity of a GaAs double quantum well between 0.5 and 1.1 K are reported. The zero magnetic-field conductivity is well described from the point of view of contributions made by both the weak localization and electron-electron interaction. At low field and low temperature, the magnetoconductivity is dominated by the weak localization effect only. Using the weak localization method, we have determined the electron dephasing times and tunne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
2
13
2
Order By: Relevance
“…However, Minkov et al [5] reported a nonmonotonic conductivity dependence of τ −1 φ , namely τ −1 φ was seen to decrease first with increasing conductivity before increasing at higher conductivity. Subsequently, Pagnossin et al [6] found that τ −1 φ is proportional to the conductivity in a GaAs double quantum well, and there is a similar observation for an InGaAs/InAlAs single quantum well [7]. These experimental results contradicting the FL model indicate that the nature of the electron dephasing in twodimensional systems is still an open question and deserves further study.…”
Section: Introductioncontrasting
confidence: 48%
“…However, Minkov et al [5] reported a nonmonotonic conductivity dependence of τ −1 φ , namely τ −1 φ was seen to decrease first with increasing conductivity before increasing at higher conductivity. Subsequently, Pagnossin et al [6] found that τ −1 φ is proportional to the conductivity in a GaAs double quantum well, and there is a similar observation for an InGaAs/InAlAs single quantum well [7]. These experimental results contradicting the FL model indicate that the nature of the electron dephasing in twodimensional systems is still an open question and deserves further study.…”
Section: Introductioncontrasting
confidence: 48%
“…Moreover, the scatterers should be common for the carriers in the different wells: each specific impurity should scatter the carriers of the lower and upper wells identically. In addition, the interwell distance d should be small, κd < 1, where κ is the inverse screening length, but the interwell transition time t 12 should be large, t 12 1/T . In reality, it is very difficult to fulfill (and especially to check the fulfillment of) all these requirements.…”
Section: Introductionmentioning
confidence: 99%
“…The correction to the conductivity due to e-e interaction 14 is investigated in DQW structures significantly less, 12,15 although it is of paramount importance in complicated systems. For instance, the effect of interaction on the conductivity has recently attracted a great deal of interest in a context of twodimensional (2D) systems with strong e-e interaction showing a metallic-type behavior of the conductivity, dσ/dT < 0.…”
Section: Introductionmentioning
confidence: 99%
“…Generally speaking, the temperature dependence of dephasing rate follows a power law, 1    ~Tp . For electron-phonon scattering mechanism 28,29 , p=2 or 4. For 7 electron-electron scattering mechanism (Nyquist dephasing mechanism) 30,29,31 , p=2 at high temperature and p=1 at low temperature (because small-energy-tranfer process usually dominates at low temperature 29,26 ).…”
mentioning
confidence: 99%
“…For electron-phonon scattering mechanism 28,29 , p=2 or 4. For 7 electron-electron scattering mechanism (Nyquist dephasing mechanism) 30,29,31 , p=2 at high temperature and p=1 at low temperature (because small-energy-tranfer process usually dominates at low temperature 29,26 ). For our data, the best fit is obtained for p=1.12 (see Fig.…”
mentioning
confidence: 99%